Peranan Media Pembelajaran dalam Memperbaiki Prestasi Belajar Siswa di MTs Negeri 2 Kepulauan Sula - Masuku, Mardiani; Kailu, Aida Surilani; Adam, Adiyana; Limatahu, Kartini (Peneliti.net, 2024)
This research aims to explore the role of learning media in improving student learning achievement at MTs Negeri 2 Sula Islands. In this context, learning media is considered a vital tool that enables the learning process to be more effective and interactive. The research background highlights the complexity of learning challenges, including loss of student focus, boredom with teaching methods, and lack of use of modern learning media. Based on Law Number 20 of 2003 concerning the National Education System, this research identifies the importance of linking theory with practice in learning, as well as how teachers can choose, prepare and use learning media effectively. Through descriptive qualitative research methods, the research results underline the importance of learning media in creating an interesting and enjoyable learning environment for students. A thorough analysis of these aspects paves the way to better learning strategies and creates meaningful learning experiences for students. This research provides in-depth insight into the complexity of student learning and provides a rich view of the integration of learning media in improving student learning achievement in educational environments